Nucleation and Growth of Dendritic Islands during Platinum Oxidation-Reduction Cycling. Issue 11 (1st November 2022) - Valls Mascaró, Francesc; McCrum, Ian T.; Koper, Marc T. M.; Rost, Marcel J.
Abstract : Platinum is the model catalyst in fuel cells because of its high activity toward oxygen reduction and hydrogen oxidation. However, its applicability is limited due to the degradation of the catalyst under operating conditions. This degradation process has been extensively studied by repeatedly oxidizing and reducing the electrode, which leads to the roughening of the surface due to the nucleation and growth of platinum nano-islands. Although the general picture of this surface roughening is well known, the atomic details concerning the nucleation and early growth of the islands are still under debate. In this work, we use Density Functional Theory (DFT) to calculate formation energies and diffusion barriers of an adatom, in both the unoxidized and the oxidized state, with the aim to provide further insight into the nucleation phenomena. Moreover, we analyze from STM images obtained experimentally the shape of the nano-islands during the first stages of growth. Our results show not only that the islands form during the reduction of the surface, but also that they grow with a dendritic island shape, similarly to the platinum islands formed in vacuum by Molecular Beam Epitaxy (MBE).